Tramas da terra: conflitos no campo na terra de Lucas, 1900-1920 - Alves, Chintamani Santana (2013)
This work has as its goal study the conflicts in the countryside, specially the fight involving ownership and propety of land and its individuals in the initial two decades of the 20th century, in Feira de Santana. We used as sources the local newspapers and mainly the processes of damage crime. Our approach was built in dialog with theoric and methodologic questions by E.P. Thompson in Whigs and Hunters, for whom the Law can be understod as a fighting arena, where the law can be seem as a way by which other social conflicts take place. So, we seek to present some delimitations and specifications in research territory, delineate the social and ethinic profile of countryside dwellers; debate family and work relationships,; point what was produced in the countrisde; investigate the existence of tension in the day-by-day life of this individuals marked by the conflicts of notions of common use and private apropriation. We identified the existence of different conceptions of right to the land that pervade the juridical partners, one based in the "soft and pacific" posse and other in the evidential right. We examinate how from the querell the complicated social relations detaches and how they constituted communitary life, being part of the conflicts themselves, specially the fight for land. By examining the countryside and their individuals we advanced into a little explored territory, the researches about Feira de Santana in this phase being more intensely dedicated to the urban part.